THE COLONIES AND THEIR QUALIFICATIONS IN THE ANCIENT GREEK (HELLENIC / ANTIK YUNAN (HELLEN)’DA KOLONILER VE BUNLARIN NITELIKLER - Ahmet Gözlü* (Folklor/Edebiyat, 2016)
This study ancient Hellenic culture and civilization in the wide geography, extensive experience as a result of expansion and special events as a process to build a colony on the stand is intended. The first groups who came to the Hellas (Greece) İndo-European origin which called Achean Greeks (Mycenaeans) they invaded the region and established the Achean confederation. Hellas, covered West Anatolian coasts and Crete Island. Achean, disseminated their culturel and commercial influence on BC 2nd millennium. Achean people of the liquidation, with the region a prevalent political authority vacuum formed, Dorians and the other Greek in length (Aeolians, İonians), this proper historical backdrop emigrated to the different parts of the Aegean region. Hellen’s geography who Hellen people lived, riven by mountains and valleys, coastal bays and coves surrounded by deep was a structure. This situation by emphasizing local fragmentation of national political authorities have prevented the integration of Hellenic around. As a result, the fragmentation of Hellen (to particularism) ‘police’ called their geographical boundaries, political institutions and laws that in the ‘city-state’ has embodied. Greece’s geograpy in terms of this fragmented situation of this country’s Division of Goverment large and small political aspects as it is also effective on the mainspring has been cultural development. Geography of Greece was a structure of local independence can be maintained easily.The Hellen’s 8 BC mid- 4th century BC a new settlement activities overseas have access to. At the head of caused of new colonization movement; Hellen’s Hell in community nutrition and livelihood challenges arising from rapid population growth, inter-party political wrangling that breed discontent and the ensuing political-induced migration has played an important role. As a result of all this ancient history of literature ‘Great Colonization Period’ as the last; Aegean, Sea of Marmara, Mediterranean and Black Sea coasts of many of the colony was founded, BC 750 to 550 between the years of 200-years period began on. The largest colony of Southern Italy and Sicily in the ‘Great Hellas’ (= Megale Hellas) was formed. At the beginning of colony-forming center, the İon cities in Western Anatolia (especially Miletus and Phocaea) was coming. The Mediterranean and the Black Sea, which surrounded around the colony and the Hellen’s here as Plato says, is like a sitting around the pool frogs are settled.